Regulation of Insulin Sensitivity by Adiponectin and its Receptors in Response to Physical Exercise - Passos, M. C. F.; Gonçalves, M. C. (Hormone and Metabolic Research, 2014)
Adiponectin is an adipocyte-derived abundant plasma protein, also called Acrp30 (adipocyte complement-related protein), adipoQ, ApM1 (AdiPose Most abundant Gene transcript 1), or GBP28 (gelatin-binding protein-28). Insulin resistance is a primary contributing factor in the pathogenesis of type 2 diabetes. Adiponectin binds to adiponectin receptors AdipoR1 and AdipoR2, and exerts antidiabetic effects via activation of AMPK and PPAR-α pathways, respectively. In the same sense chronic exercise has been showed to induce numerous metabolic factors that can improve insulin resistance. It has been reported that physical exercise training increases adiponectin receptors, which may mediate the improvement of insulin resistance in response to exercise, which is the focus of the present review.
Keywords: adiponectin; receptors; insulin resistance; exercise